WIDENING THE CIRCE OF CLAIMS WITH A ONE-YEAR STATUTE OF LIMITATIONS - Pilipović, Dejan (Glasnik Advokatske komore Vojvodine, 2021)
The author of this paper analyses the possibility of the analogous application of article 378 of the Contracts and Torts Act (CTA) on other similar (same) claims. The aim of this study is to give an answer to the central question of whether it is necessary to improve CTA provisions regarding one-year claims limitation period in compliance with modern trends considered from the angle of claims which are to expire within the stated period. In order to give a valid answer to this question the author uses certain scientific and research methods, i.e. techniques, such as dogmatic and normative, legal history, comparative law, analysis of the content and a questionnaire. Such mechanism is used in the process of studying legislation, case law, and legal theory, the same being used during empirical research. Knowing the circle of claims that have a one-year limitation period is important not only for theoretical analysis, but also for court practices, and consumers.
Keywords: statute of limitations; one-year limitation period; Contracts and Torts Act; circle of claims; consumers